2009
DOI: 10.1016/j.juro.2009.08.044
|View full text |Cite
|
Sign up to set email alerts
|

Serial Prostate Biopsies are Associated With an Increased Risk of Erectile Dysfunction in Men With Prostate Cancer on Active Surveillance

Abstract: Serial prostate biopsies appear to have an adverse effect on erectile function in men with prostate cancer on active surveillance but do not affect lower urinary tract symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
106
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(112 citation statements)
references
References 22 publications
2
106
2
2
Order By: Relevance
“…4 Recently, there have been studies investigating urinary and erectile function after prostate biopsy. 2,3,5 There are few publications on preoperative and postoperative impact of serial prostate biopsies on active surveillance patients who ultimately undergo RARP. 5 This is especially relevant as one-third of men enrolled in AS may eventually require definitive surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Recently, there have been studies investigating urinary and erectile function after prostate biopsy. 2,3,5 There are few publications on preoperative and postoperative impact of serial prostate biopsies on active surveillance patients who ultimately undergo RARP. 5 This is especially relevant as one-third of men enrolled in AS may eventually require definitive surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Fujita et al 2 retrospectively analyzed 231 active surveillance patients to compare whether there was a correlation between increased number of biopsies and ED. Increased biopsy number was associated with a decrease in Sexual Health Inventory for Men score (P ¼ 0.04) and a history of three or more biopsies was associated with a greater decrease in sexual health inventory for men than after two or fewer biopsies (P ¼ 0.02).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a significant number of patients may be found to have prostate cancer on repeat biopsy, 1,2 the potential morbidity of prostate biopsy must be considered. 3 A recent population-based study of Canadian men reported a 30-day hospital admission rate of 4.1% and a mortality rate of 0.9% due to biopsy-related complications. 4 We present an evaluation of PCA3 as a univariable predictor of prostate cancer on repeat biopsy and as a component of a multivariable nomogram.…”
Section: Discussionmentioning
confidence: 99%
“…In all, 10-39% of such patients may ultimately be found to have prostate cancer on repeat biopsy. 1,2 However, prostate biopsy is uncomfortable and can carry significant morbidity, 3,4 and most men who undergo repeat biopsy are ultimately found to be free of prostate cancer. Additionally, the probability of having a positive biopsy decreases with each subsequent biopsy.…”
Section: Introductionmentioning
confidence: 99%